Constitutive structural parameter cb for the work‐hardening behavior of laser powder‐bed fusion, additively manufactured 316L stainless steel. Issue 6 (19th January 2020) - Jankowski, Alan F.; Yang, Nancy; Lu, Wei‐Yang
Abstract: The mechanical behavior of additively manufactured (AM) 316L produced by laser powder‐bed fusion (LPBF) process is now assessed using a work‐hardening model that is derivative from the Kocks‐Mecking (K‐M) relationship. A constitutive parameter c b for the microstructure is derived that is representative of the work‐hardening behavior, as determined by the plastic strain ε p between the yield point σ y and ultimate strength σ u . The varied mechanical response that can be representative of AM metal behavior, as associated with surface irregularities and build direction, can be evaluated with this approach. Results are presented for the mechanical behavior of a 316L stainless steel as evaluated through uniaxial tensile test measurements.